2021
DOI: 10.1177/1071181321651266
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Perception Of Training Approaches For Advanced Driver Assistance Systems (Adas)

Abstract: Advanced Driver Assistance Systems (ADAS) provide safety and comfort while driving. However, to effectively use ADAS, it is necessary for users to have proper knowledge of the systems and to trust the system to operate safely. Providing knowledge about operational capabilities and limitations of a system may help improve drivers’ mental models and calibrate their trust resulting in proper use of ADAS. Traditionally system information is provided via the owner’s manual, which is known to be tedious and time-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Training has been shown to be effective in accelerating higher-order skills and knowledge in traditional driving (Pradhan et al, 2011). In a past study training was found to help calibrate trust and confidence, although in this study the improvement of knowledge and driver responses were not measured (Pai et al, 2021). However, training has an important role and is gaining recognition as a potentially critical tool for improving drivers' knowledge, understanding, and appropriate use of advanced vehicle technologies (Pradhan et al, 2019).…”
Section: Introductionmentioning
confidence: 80%
“…Training has been shown to be effective in accelerating higher-order skills and knowledge in traditional driving (Pradhan et al, 2011). In a past study training was found to help calibrate trust and confidence, although in this study the improvement of knowledge and driver responses were not measured (Pai et al, 2021). However, training has an important role and is gaining recognition as a potentially critical tool for improving drivers' knowledge, understanding, and appropriate use of advanced vehicle technologies (Pradhan et al, 2019).…”
Section: Introductionmentioning
confidence: 80%
“…Previous work has reported that training did not have any impact on the user's post-training overall trust scores (Pai et al, 2021). However, it is unknown if there is a relationship between the mental models scores and overall trust scores.…”
Section: Correlation Between Overall Mental Model Survey and Trust Sc...mentioning
confidence: 93%